1995
DOI: 10.1093/nar/23.19.3901
|View full text |Cite
|
Sign up to set email alerts
|

The orientation of binding of human immunodeficiency virus reverse transcriptase on nucleic acid hybrids

Abstract: The binding of HIV reverse transcriptase (RT) to heteroduplexes was examined using a substrate consisting of a 42 nt chimeric nucleic acid composed. (5'-->3') of 23 nt of RNA and 19 of DNA. This chimera was hybridized to an internal region of a relatively long complementary DNA or RNA. When the chimera was bound to DNA and conditions limiting cleavage to a single binding event between the enzyme and substrate were employed initial RNase H-directed cleavages occurred 19-21 nt from the chimera 5'-terminus. A 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 29 publications
(32 reference statements)
4
45
0
Order By: Relevance
“…6, A-C, lanes 1). If cleavage were directed by binding to the 5Ј terminus of the RNA, it would occur at a position approximately 18 nt downstream (22). With the 20-nt RNA, this would place the cleavage site 2 bases upstream of the RNA-DNA junction, leading to a 17-nt labeled product; with the 25-nt RNA, cleavage would occur 2 bases within the PPT and would result in a labeled product of 22 nt.…”
Section: Resultsmentioning
confidence: 99%
“…6, A-C, lanes 1). If cleavage were directed by binding to the 5Ј terminus of the RNA, it would occur at a position approximately 18 nt downstream (22). With the 20-nt RNA, this would place the cleavage site 2 bases upstream of the RNA-DNA junction, leading to a 17-nt labeled product; with the 25-nt RNA, cleavage would occur 2 bases within the PPT and would result in a labeled product of 22 nt.…”
Section: Resultsmentioning
confidence: 99%
“…Although site H was not cleaved in Md1 or Md2, this site was detectably cleaved between the 19th and 20th nucleotides in substrate Md4 (lanes [11][12][13][14][15] and significantly cleaved between the 17th and 18th nucleotides in substrate Md6 (lanes 16 -20). No cleavage was observed at site I in substrates Md1 through Md7 (lanes 1-25), but this site was cleaved when located between the 19th and 20th nucleotides in substrate Md9 and between the 18th and 19th nucleotides in substrate Md10 (lanes [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Sequence and Distance Are Determinants Of Rna 5ј-end-directedmentioning
confidence: 99%
“…Most likely this is because prior studies utilized a limited number of RNAs and thus had very little variation in sequence (21, 29, 32, 38 -43). Also for several studies, the precise mapping of RNA 5Ј-enddirected cleavage sites was often difficult or not required by the experimental design (21,29,32,46). Most recently, RNA 5Ј-end-directed cleavages have been examined with regard to the order of cleavage that occurs on an RNA/DNA hybrid with a recessed RNA 5Ј-end (38 -40).…”
Section: Volume 281 • Number 4 • January 27 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…The third structure, the strand transfer intermediate, contains both the donor and acceptor RNAs bound to DNA. Previous results have indicated that RT is anchored to nucleic acid substrates by a 3Ј recessed DNA terminus or a 5Ј recessed RNA terminus (7)(8)(9)(10)(11)(12)(13). With this in mind, RT would be expected to bind preferentially to the donor RNA of the trimer, because the 3Ј-end of the DNA strand is recessed on the donor RNA.…”
mentioning
confidence: 99%